Expression of Hypoxia-Inducible Factor (HIF)-1α and Vascular Endothelial Growth Factor (VEGF)-D As Outcome Predictors in Resected Esophageal Squamous Cell Carcinoma. Issue 3 (4th June 2013) - Tzao, Ching; Lee, Shih-Chun; Tung, Ho-Jui; Hsu, Han-Shui; Hsu, Wen-Hu; Sun, Guang-Huan; Yu, Cheng-Ping; Jin, Jong-Shiaw; Cheng, Yeung-Leung
Abstract : Hypoxia-inducible factor (HIF)-1 α and vascular endothelial growth factor (VEGF) are important angiogenic factors in human cancers. Relative to VEGF-C, prognostic significance of VEGF-D expression and its association with HIF-1 α expression remain elusive in esophageal squamous cell cancer (ESCC). We studied expression of HIF-1 α and VEGF-D using immunohistochemistry in 85 resected ESCC specimens and correlated results with patients' clinicopathologic parameters and survival. Association between expression of HIF-1 α and VEGF-D was investigated using a concordance analysis. High expression of HIF-1 α and VEGF-D was observed in 52 (61.2%) and 56 (65.9%) patients, respectively. HIF-1 α expression correlated well with tumor stage ( P = 0.041), whereas VEGF-D expression correlated with tumor stage ( P = 0.027) and N status ( P = 0.019). Groups of high HIF-1 α and VEGF-D showed worse survivals than those of low expression ( P = 0.002 and 0.001, respectively). Multivariate analysis supported expression of HIF-1 α and VEGF-D as significant survival predictors ( P = 0.044 and 0.035, respectively). A concordance rate of 69.5% was observed between expression of HIF-1 α and VEGF-D. In conclusion, protein expression of HIF-1 α and VEGF-D are independent prognostic predictors. An association between expression of HIF-1 α and VEGF-D suggests that these two angiogenic factors are essential in progression of ESCC.